A Simplified Analysis and Design of an RCD Clamp Forward Converter - Wuti, Virot; Trakuldit, Siripan; Luangpol, Amata; Tattiwong, Kaweewat; Taylim, Alisala; Bunlaksananusorn, Chanin (My University, 2022)
A conventional forward converter requires a transformer having an extra winding to assist in magnetic core reset, thus complicating the design and increasing the production cost. These shortcomings can be overcome by using an RCD clamp forward converter. This article presents a simplified analysis and design of the RCD clamp forward converter. The laboratory prototype is constructed. Experimental results demonstrates that the prototype converter is capable of providing a constant output voltage throughout its operating condition and has the maximum efficiency of 85%.
Keywords: DC-DC converter; RCD clamp forward converter